Topographic corneal changes in children with vernal keratoconjunctivitis: A report from Kathmandu, Nepal. Issue 6 (December 2015) - Gautam, Vijay; Chaudhary, Meenu; Sharma, Ananda Kumar; Shrestha, Gauri Shankar; Rai, Pooja Gautam
Abstract: Purpose: The present study was conducted to determine corneal topographic characteristics of children with vernal keratoconjunctivitis (VKC) and compare the corneal topographic indices in VKC subjects with normal subjects Material and method: In the hospital based comparative study, 115 consecutive subjects with VKC and 102 age and sex matched normal subjects were selected for the videokeratography with NIDEK ophthalmic operating system. Keratoconus-like topography was determined based on the expert classifier system. Other assessments included visual acuity testing with LogMAR chart, slit lamp biomicroscopy, dilated fundus examination, measurement of central corneal thickness and intraocular pressure. Topographic indices were analyzed and compared using unpaired t -test among different groups. Sensitivity and specificity was estimated by the ROC curve. Result: Among 115 subjects with VKC, males comprised of 86 subjects (66.1%) and mean age of presentation was 10.9 (SD 4.9) years with mixed VKC in 56.5%. Keratoconus-like topography was present in 13 subjects (11.3%). The keratoconus predictiv index (sensitivity 92.3%, specificity 98.5%), the opposite sectoral index (sensitivity 84.6%; specificity 93.2%), the differential sectoral index (sensitivity 92.3%; specificity 90.8%) were found to be signficantly associated with VKC subjects having keratoconus-like topography. Conclusion: A high prevalence of keratoconus-like topography was observed in patients with VKC.